Plant-specific VQ-domain proteins as interaction partners of WRKY transcription factors. (16th July 2014) - Kwon, Soon Il; Hwang, D. J.
Abstract : VQ-domain proteins are known to interact with WRKY transcription factors and have been reported to be involved in plant defence responses to environmental stresses in Arabidopsis . Thus, elucidation of the defence mechanisms during the interaction of VQ-domain proteins and WRKY transcription factors could provide useful insights into the regulation of VQ-domain protein-mediated WRKY transcription factors. As the focus of this review, we summarize the genomic analysis of the VQ-domain proteins as one of the WRKY-interacting proteins and their biological effects during plant stress conditions in Arabidopsis and rice.